Assessing Physical Activity and its Relationship to Cardiovascular Risk Factors: NHANES 2003-2006 - Cao Guichan; Durazo-Arvizu Ramon A; Dugas Lara R; Luke Amy; Cooper Richard S (BMC, 2011)
Abstract Background Levels of physical activity (PA) in the general population are difficult to characterize. Historically measurement has been based on self-report, which can be subject to bias. PA monitor use has created opportunities to improve surveillance and analytic research on activity and health. The aims of the current study were to investigate the associations between objectively measured PA and cardiovascular disease risk factors and obesity. Methods Data on PA from accelerometers, demographics, blood pressure, plasma glucose and lipids, self-reported hypertension and diabetes were obtained for adults, ages 20-65, in the NHANES surveys, 2003-2006. Outcomes were assessed as levels of moderate and vigorous activity, percentage of participants meeting recommended guidelines, and the correlations between activity and cardiovascular risk factors. Accelerometry data were available on 3,370 adults. Based on standard algorithms, activity levels were extremely low in all age-gender-race/ethnic groups, with an average of only 1 bout of vigorous activity lasting longer than 1 minute/day. Results Men spent 35 minutes in moderate activity/day, women 21 minutes; >75% of this activity was accumulated in 1-minute bouts. Levels of activity declined sharply after age 50 in all groups. Negative associations were observed between minutes of combined moderate and vigorous activity and systolic blood pressure, blood glucose, diabetes, hypertension, body mass index and obesity, and a positive association was seen with HDL-cholesterol (all P ≤ 0.03), suggesting valid rank ordering of participants by activity level. Conclusion The magnitude of the gap between self-report and accelerometry activity must be a result of either a vast social acceptability bias in reporting or inaccurate measurement with accelerometry. Therefore, due to the low validity of self reported PA data for epidemiologic research, it is pertinent to encourage the use of valid, objective methods to assess PA.